Access to imaging investigation and neurosurgical care is delayed in regional Queensland for paediatric primary brain tumours. (May 2022) - Mills, Sarah; Vile, Alexander; Campbell, Robert; Chaseling, Raymond
Highlights: Paediatric brain tumours are number one cause of oncology mortality. Children in remote and rural locations have a significant delay to their diagnosis. Significant delay from first presentation to medical imaging. No delay from medical imaging to neurosurgical review and intervention. No significant consequence to mortality but possible morbidity. Abstract: Central nervous system tumours are the leading oncology cause of paediatric mortality. The aim of this research was to identify stages within the diagnostic process of a primary paediatric brain tumour that could be improved resulting in better outcomes. Methods: The electronic medical records of Queensland Children's Hospital patients with central nervous system tumours between the 17/12/2014 till 11/12/2019 were retrospectively accessed. Time intervals of symptom onset to first medical review,  location, time till medical imaging,  subspecialty or neurosurgical review, timing of surgery, diagnosis and mortality status were recorded then analysed. Results: A total of 168 patients were included. Mean age to 7.5, 65% male, with pilocytic astrocytoma representing 31%. 71.4% of the population were from a major city as determined by Remoteness Area classification, ABS, with 19% inner regional and 9.5% being outer regional and remote. The average time from first medical review to diagnostic imaging was significantly different when comparing remoteness classification (p = 0.044). There was also a statistically significant difference in the duration of time from medical imaging to specialist review comparing major city and outer regional/remote (p = 0.016) and inner regional versus outer regional/remote areas (p = 0.026). Conclusions: Delays in imaging in outer regional and remote Queensland are contributing to a delay in diagnosis and intervention in paediatric brain tumours. Service provision for neurosurgery in outer regional and remote Queensland is currently on par with inner regional and city areas. Suspicion of paediatric brain tumours is needed with clear referral pathways for general practitioners to access diagnostic imaging.